Synthesis and Crystal Structure of 3-Bromo-2- hydroxybenzaldehyde-2-pyridinecarboxylic acid hydrazone. Issue 5 (January 2021) - Zhao, Meili
Abstract: A new hydrazone compound, 3-bromo-2-hydroxybenzaldehyde-2-pyridinecarboxylic acid hydrazone (1), has been synthesized with 3-bromo-2-hydroxybenzaldehyde and 2-pyridinecarboxylic acid hydrazide as raw materials in the presence of magnesium chloride hexahydrate. The result of structural analyses shows that the compound 1 belongs to monoclinic, space group P121 /c1 (no. 14) with a = 15.8346(13) Â, b = 6.9597(5) Â, c = 12.1912(13) Â, β = 109.123(10)°, V = 1269.4(2) Â 3, Z = 4, Dc = 1.675 mg⋅m -3, μ = 3.239 mm -1, F (000) = 640, and final R1 = 0.0538, ωR2 = 0.0896.